Endogenous ADP-Ribosylation - Koch-Nolte, Friedrich (Current Topics in Microbiology and Immunology, 2015)
This volume gathers the latest exciting findings on ADP-ribosylation from renowned experts in the field. It includes ten chapters, organized into the following three thematic sections:  ·   Evolution and detection of endogenous ADP-ribosylation  ·   ADP-ribosylation by the ARTC family of ADP-ribosyltransferases (R-S-E ARTs)   ·   ADP-ribosylation by the ARTD family of ADP-ribosyltransferases (H-Y-E ARTs) The book will provide readers a better understanding of ADP-ribosylating toxins and their endogenous relatives. This provides a basis for developing novel toxin-neutralizing drugs and drugs targeting endogenous ADP-ribosyltransferase relatives.